Greening Healthcare Spaces: Carbon cost of tree loss in public healthcare facilities - Borhan, Ruwaidah; Ghani, Izham; Abdul Rahman, Norhafizah; Heath, Tim (Environment-Behaviour Proceedings Journal, 2025)
This study examines the environmental implications of landscape design decisions in Malaysian healthcare settings, with a focus on carbon storage loss resulting from the removal of mature trees. A quantitative analysis involving tree inventories, carbon estimations, and site documentation identified a carbon loss of approximately 1.8 tonnes of CO₂ due to the replacement of green walls and ornamental shrubs. The findings reveal inconsistent, aesthetics-driven practices that neglect long-term ecological functions. This study highlights the urgent need for standardised landscape guidelines that integrate carbon accounting and mature tree preservation, thereby contributing to sustainable hospital development and national environmental resilience goals.